You are on page 1of 5

Task I

Mathematical Induction.
Prove each of the following:
1. 1 + 3 + 5….+(2n-1) = n2
Solution:
1=12 (n=1, assumption)
n=k (1+3+5…+(2k-1)=k2 , assumption)
Now,
Putting the above value in given,
1+3+5…+(2k-1)+2(k+1)-1=(k+1)2
As we know that,
1+3+5…+(2k-1)=k2 (the assumption above)
Here,
K2+2(k+1)-1=(k+1)2
k2+2k+2-1=k2+2k+1 (by expanding)
k2+2k+1=k2+2k+1 (they are same)
Therefore, 1+2+3+…2(k+1)-1=(k+1)2 i.e. 1 + 3 + 5….+(2n-1) = n2 proved.

1 1 1 1 𝑛
2. + + + ⋯ + (2𝑛−1)(2𝑛+1) =
1.3 3.5 5.7 (2𝑛+1)
Solution,
Put n=1
1 1
P(1)=1/3 = = (which is true)
(2+1) 3
Assuming that true of p(k)
1 1 1 1 𝑘
P(k): + + + ⋯ + (2𝑛−1)(2𝑛+1) = (2𝑘+1)
1.3 3.5 5.7
(k+1)
Let p :
1 1 1 1 1
+ + +⋯+ +
1.3 3.5 5.7 (2𝑘 − 1)(2𝑘 + 1) (2(𝑘 + 1) − 1)(2(𝑘 + 1) + 1
𝑘 1
= +
(2𝑘+1) (2(𝑘+1)−1)(2(𝑘+1)+1
𝑘 1
= (2𝑘+1) + (2𝑘+2−1)(2𝑘+2+1)
𝑘 1
= (2𝑘+1) + (2𝑘+1)(2𝑘+3)
𝑘(2𝑘+3)+1
= (2𝑘+1)(2𝑘+3)
2𝑘 2 +3𝑘+1
= (2𝑘+1)(2𝑘+3)
2𝑘 2 +2𝑘+𝑘+1
= (2𝑘+1)(2𝑘+3)
2𝑘(𝑘+1)+(𝑘+1)
= (2𝑘+1)(2𝑘+3)
(2𝑘+1)+(𝑘+1)
= (2𝑘+1)(2𝑘+3)
(𝑘+1)
= (2𝑘+3)
Hence, by using principle of mathematical induction true for all n ∈ N.

1 1 1 1 𝑛
3. + + + ⋯ + (2𝑛−1)(2𝑛+1) = (2𝑛+1)
1.3 3.5 5.7
1 1 1 1 𝑛
Let P(n): + + + ⋯ + (2𝑛−1)(2𝑛+1) = (2𝑛+1)
1.3 3.5 5.7
For n=1,
1 1 1 1 1 1
L.H.S = + + + ⋯ + (2𝑛−1)(2𝑛+1) = =
1.3 3.5 5.7 1.3 3
𝑛 1 1
R.H.S = (2𝑛+1) = (2.1+1) =
3
Hence, L.H.S =RHS
Therefore, P(n) is true for n, where n is a natural number.

Task II
1) Complex number polar form.
Perform each of the indicated operations:
a. 2 (5-3i) -3 (-2+i) + 5 (i-3)
= 10 – 6i + 6 – 3i + 5i – 3
= 1 – 4i i.e. Z= a + ib
b. (3 – 2i)3
= (3)3 – 3 × (3)2 × (-2i) + 3 × (3) (-2i)2 – (-2i)3
= 27 + 54i + (-36) × (-1) – (-8i)
= 27 + 54i + 36 + 8i = 63 + 62i = i.e. Z= a + ib
5 10
c. +
3 + 4𝑖 4 + 3𝑖

5(4 + 3𝑖)+10 (3 + 4𝑖)


= (3− 4𝑖) (4 + 3𝑖)
20+15𝑖+30−40𝑖
=
12+9𝑖−16𝑖+12
50−25𝑖
= .
24−7𝑖

1−𝑖
d. ( )10
1+𝑖
1−𝑖 1−𝑖
={ × ( )}10
1+𝑖 1−𝑖
( 1−𝑖 )2
= {(1+𝑖)( }10
1−𝑖 )
( 1 )2 −2 ×1 ( 𝑖 )+( 1 )2 10
= { }
12 − 𝑖 2
1+2𝑖−1 10
={ }
1+ 1
2i 10
={1+ }
2
= ( 𝑖 )10
= i2 × i2 × i2 × i2 × i2
= (−1) × (−1) × (−1) × (−1) × (−1)
= -1 .

2) Express in polar form:


a. 3√3 + 3i
Solution:
Comparing given equation with z=x + iy, Z = r (cosθ + i sinθ ).
Then,
x= 3√3, y= 3
now, we know that

r = √𝑥 2 + 𝑦 2 = √(3√3)2 + (3)2 = 6.
𝑦
θ = tan θ -1 ( ⁄𝑥) = tan θ -1 (3⁄ ) = 𝑟⁄6
3√3
Substituting value of θ and r in Z = r (cosθ + i sinθ ) = 6 (cos 𝑟⁄6 + 𝑖 sin 𝑟⁄6).
b. -2 – 2i
Solution:
Z = r (cosθ + i sinθ )
Comparing given equation with x + iy then,
We have x = -2 y= -2
Now,
r =√𝑥 2 + 𝑦 2 = √(−2)2 + (2)2 = 2√2
𝑦
θ = tan θ -1 ( ⁄𝑥) = tan θ -1 (−2⁄−2) = tan θ -1 (1) = tan θ -1 (tan 𝑟⁄4) = r/4 .
Substituting value of θ and r in Z = r (cosθ + i sinθ )
= 2√2 (cos 𝑟⁄4 + 𝑖 sin 𝑟⁄4).

c. 1 - √3 𝑖
Solution:
Z = r (cosθ + i sinθ )
Comparing given equation with x + iy then,
We have x = 1 y= √3
Now,
r =√𝑥 2 + 𝑦 2 = √(1)2 + (−3)2 = √10
𝑦
θ = tan θ -1 ( ⁄𝑥) = tan θ -1 (−√3⁄1) = 5r/3.
Substituting value of θ and r in Z = r (cosθ + i sinθ )
= √10 (cos 𝑟⁄3 + 𝑖 sin 𝑟⁄3).

d. 5
Solution,
Z = r (cosθ + i sinθ )
The above equation can be written as z= 5 + 0 × 𝑖, Z = r (cosθ + i sinθ )
Now,
r =√𝑥 2 + 𝑦 2 = √(5)2 + (0)2 = 5
𝑦
θ = tan θ -1 ( ⁄𝑥) = tan θ -1 (0⁄5) = 0
Substituting value of θ and r in Z = r (cosθ + i sinθ )
= 5 (cos 0 + 𝑖 sin 0).
e. -5i
Solution:
Z = r (cosθ + i sinθ )
Placing above equation as Z= 0 – 5i i.e. Z = r (cosθ + i sinθ )
Then, we have X= 0, Y = -5
r =√𝑥 2 + 𝑦 2 = √(0)2 + (−5)2 = −5.
𝑦
θ = tan θ -1 ( ⁄𝑥) = tan θ -1 (−5⁄0) = (𝑟⁄2).
Substituting value of θ and r in Z = r (cosθ + i sinθ )
= 5 (cos 𝑟⁄2 + 𝑖 sin 𝑟⁄2).

You might also like